PILIHAN BAHASA REMAJA SASAK KOTA MATARAM - Wiya Suktiningsih (RETORIKA: Jurnal Ilmu Bahasa, 2017)
Abstract The language aspects and social context outside of the language which are related effect the linguistic situation of a multilingual society. This study was conducted to see how the process of language choice among teens of Sasak and factors that influence it. Teen's of Sasak as Sasak speakers learn Bahasa when they started education. Second language acquisition in education domain influence the language choice among teen’s of Sasak. This situation are very interesting topic to reviewed by using theory in sociolinguistics approach. The research is aimed to identify the language choice factors among teen’s of Sasak in speech event. This research is qualitative research used the data were collected using the methods of observation, recording, and interview. The sample used is 70 teen's of Sasak were in the range of 18 to 23 years who live in Mataram city and a student. The findings out the research revealed that, First : The language situation of Mataram city society is the background of the Language selection process. Second: This research do observations in four domains of language used, family, neighbors, education and religion. Third: This research findings three major factors as affecting the speaker language in social interactions, (1) the setting (time and place) and the situation; (2) participants/audience in the interaction, (3) the topic of conversation. Keywords: Language choice ,language acquisition, domain and sosiolinguistics